Some connotations of faith, moral, mental, advocacy and professional derived from surat Alhijr and its educational applications. - Al Qathami, Awatif Mansour Bakhit (Journal of Educational and Psychological Sciences, 2018)
This study aims to know some of the derived purports in the verses of Surah Al-Hijr and its applications in education, the study dealt with several topics, included definition of Surah Al-Hijr, revealing some of the purports of Surah Al-Hijr such as worshipping, moral, mental, etc. and also it dealt with their applications in the families. The researcher used the descriptive and deductive method in the preparation of this study. One of the most important results in this study is that Surah Al-Hijr implanted in the Muslims hearts, the Islamic religion, where it is the reason for their goodness and integrity. Islam warns against the use of mental measurement in a wrong and corrupt way which opposes the Islamic religion. The miracle of God Almighty in creation of human being has been mentioned in his Quran, where the modern science proved that miracle and the human body consists of elements which similar to the chemical composition of soil mixed with water, where at death the human body turns into dust. The study comes up with number of recommendations: The experts in the Curriculum and Development Department at the Ministry of Education should give more attention to the methodology of Islamic faith and to the polytheism subjects in the modern era. The importance of performing a field study on the educational methods to counteract the outsider creedal thought through participation of professors in the Faculty of Education at the University of Jeddah.